Imaging Evil in the First Chapters of Genesis: Texts behind the Images in Eastern Orthodox Art - Kuyumdzhieva, Margarita (Studia Ceranea, 2016)
Satan’s interference in the events described in the first chapters of the book of Genesis and in the life of the protoplasts is not mentioned at all in the biblical text. This happens, however, in pseudo-canonical texts. The article is a short survey on the apocryphal accounts that mention Satan and their influence on art. The main focus is put on the inclusion of the image of Satan behind Cain’s figure in a number of depictions of the scene The Murder of Abel in the Russian art of the 16th and 17th centuries. The possible links between this visual motif with several literary sources is examined, among them the Short and the Explanatory Palaea, the Tale of Bygone Years (Povest’ vremennykh let or Primary Chronicle), Russian recensions of the apocryphon The Sea of Tiberias, and of The Revelation of Pseudo-Methodius of Patara. In addition, some instances of the same visual decision in Balkan art are pointed out and their connection to Russian models is underlined.